Ecdysteroid-dependent expression of the tweedle and peroxidase genes during adult cuticle formation in the honey bee, Apis mellifera. - Michelle P M Soares (Public Library of Science (PLoS), 2011)
Cuticle renewal is a complex biological process that depends on the cross talk between hormone levels and gene expression. This study characterized the expression of two genes encoding cuticle proteins sharing the four conserved amino acid blocks of the Tweedle family, AmelTwdl1 and AmelTwdl2, and a gene encoding a cuticle peroxidase containing the Animal haem peroxidase domain, Ampxd, in the honey bee. Gene sequencing and annotation validated the formerly predicted tweedle genes, and revealed a novel gene, Ampxd, in the honey bee genome. Expression of these genes was studied in the context of the ecdysteroid-coordinated pupal-to-adult molt, and in different tissues. Higher transcript levels were detected in the integument after the ecdysteroid peak that induces apolysis, coinciding with the synthesis and deposition of the adult exoskeleton and its early differentiation. The effect of this hormone was confirmed in vivo by tying a ligature between the thorax and abdomen of early pupae to prevent the abdominal integument from coming in contact with ecdysteroids released from the prothoracic gland. This procedure impaired the natural increase in transcript levels in the abdominal integument. Both tweedle genes were expressed at higher levels in the empty gut than in the thoracic integument and trachea of pharate adults. In contrast, Ampxd transcripts were found in higher levels in the thoracic integument and trachea than in the gut. Together, the data strongly suggest that these three genes play roles in ecdysteroid-dependent exoskeleton construction and differentiation and also point to a possible role for the two tweedle genes in the formation of the cuticle (peritrophic membrane) that internally lines the gut.